Evaluation of culinary Musa germplasm for fibre yield and quality - UMA, S; KALPANA, S; SARASWATHI, M S; DURAI, P; KUMAR, V (The Indian Journal of Agricultural Sciences, 2011)
A trial was conducted during 280143 to evaluate 50 Indian culinary banana varieties for their suitability to fibre extraction and various methods of extraction. More than 50% of the cultivars grown in Indian subcontinent are suitable for fibre extraction as they exhibited high fibre yield. Of these highest fibre yield was exhibited by varieties, like ’Enna Benian’ (0.96%), ’Singhlal’ (0.67%) and ’Monthan’ (0.68%). Quality in terms of brightness, moisture, lignin and cellulose contents was best in ’Singhlal’, ’Mallu Monthan’, ’Kullap Kunnara’, ’Enna Benian’, ’Manja Vazhai’ and ’Shakl Kela’. Among the different methods of extraction, machne extraction gave 25% higher fibre yield than the manual extraction while fibre quality was better in manually extracted fibre.